Improving Students Reading Comprehension Through Probing-Prompting Technique At The Eighth Grade Of SMP Negeri 4 Pancarijang - Ince Nasrullah; Lababa Lababa; Nadirah Nadirah; Yusrianti Yusrianti; Hartati Hartati (La Ogi : English Language Journal, 2023)
The objective of the research are find out whether or not the use of Probing- Pompting Technique improves te students reading comprehension and student interest at the eighth grade of SMP Negeri 4 Pancarijang. His research employed pre- experimental method with on group pre-test and post-test design. The population was Theeighth grade student of SMP Negeri 4 Pancarijang in academic 2014-2015. Total number of population was 66 student consist of 3 classes and one class (VIII.2) was taken as sample by using cluster sampling techniquetotal of sample 20 students’. The research instrument are reading test an questionnaire. The result this research showed that the pre-test got the mean score (56.00) while the post-test goat mean score (69.00). This showed that there was significant difference between pretest and posttest. The result of the t-test value (5.378) was higher than t-table (2.093). This mean that H1was accepted. The researcher concluded that teaching reading comprehension by using probing-prompting increased the students’ ability in reading comprehension of SMP Negeri 4 Pancarijangand the mean score of the questionnaire was 84.75 categorized as a strongly interested. The researcher concluded that teaching reading comprehension by using probing-prompting improve the students’ ability in reading comprehension at the eighth grade SMP negei 4 Pancarijang